Pengaruh Gaya Mengajar Guru Terhadap Motivasi Belajar Peserta Didik Kelas Tinggi Sekolah Dasar (IAIN Kendari, 2023)
This survey research aims to understand the teaching styles of teachers at SDN 12 Tongkuno, ascertain the level of the students' learning motivation, and determine the influence of teachers' teaching styles on the students' learning motivation. Utilizing the stratified random sampling technique, a sample of 43 students was selected from a population of 76 students in grades IV, V, VI. The research data, collected through questionnaires and documentation, were analyzed using descriptive statistics and inferential statistical analysis. The findings reveal that, among the four categories of teaching styles, two categories – classical and technological teaching styles – are rated high. The other two categories, personalization and interactional styles, are at a medium level. Similarly, both intrinsic and extrinsic motivation categories are at a medium level. Furthermore, the teachers' teaching style has been proven to have a positive and significant impact on the students' learning motivation at SDN 12 Tongkuno, contributing 38.3% to their motivation. The better the teaching style of the teachers, the higher the students' learning motivation at SDN 12 Tongkuno, Muna District.Keywords: Teacher’s teaching style, student’s learning motivation, upper class of elementary school